Survey on time‐domain power theories and their applications for renewable energy integration in smart‐grids. Issue 4 (11th July 2019) - Godoy Simões, Marcelo; Harirchi, Farnaz; Babakmehr, Mohammad
Abstract : The increasing aggregation of renewable‐based distributed generating units besides the impressive growing usage of non‐linear loads raises unwanted challenges for traditional power terms definition in power engineering. This fact consequently affected the performance of the conventional control frameworks and industrial compensation techniques. In this study, the authors aim to provide an insightful summary over the most recognised time domain‐based instantaneous power theories and discuss their advantages and disadvantages within a comprehensive mathematical‐conceptual and applicational framework for professionals who are using instantaneous power theories within the smart grid applications. They conclude that there is still a need for a modified power theory which can be validated under non‐sinusoidal‐unbalanced load/source conditions respecting the physical meaning of different power and current components.